Designing the syntheses and photophysical simulations of noncentrosymmetric compounds. Issue 2 (24th December 2014) - Cheng, Wen-Dan; Lin, Chen-Sheng; Luo, Zhong-Zhen; Zhang, Hao
Abstract : The designs of NCS compounds based on the normal development of NCS chromophores are presented and NLO properties are investigated. Abstract : In this paper, we describe the preparations of inorganic noncentrosymmetric (NCS) chalcogenides and their infrared nonlinear optical properties. We present a reasonable synthesis of inorganic NCS compounds by considering the genetic development processes of a living organism. The basic unit having an NCS structure is selected as a chromophore of NCS materials. The NCS compounds are obtained from the NCS chromophore development of normal growth. Chromophore development is an alienation process of growth if the NCS compound is not formed by an NCS chromophore. The normal development of the NCS chromophores (SnS4 ) and (Sn2 S3 ) affords the NCS crystal of Ba7 Sn5 S15 ; and the normal development of the NCS chromophores of (BiS5 ) and (InS4 ) affords a compound of Ba2 BiInS5 maintaining an NCS structure. In both of them, the Ba 2+ ions are a charge-compensating agent. The NCS crystals SnGa4 Q7 (Q = S, Se) were obtained from NCS chromophores of (GaQ4 ) and (SnQ4 ). However, the centrosymmetric (CS) compound of Ba6 Sn7 S20 was obtained because the development of NCS chromophores of the (SnS4 ) and (SnS5 ) is alienated from the normal process of growth. We give more examples of the NCS chromophore development of normal and alienable processes in this paper. For NCS compounds, we have examined their nonlinear optical (NLO) properties of micro-crystals (powders) and the electronic origin of the NLO response. The intensity of second harmonic generation (SHG), laser-induced damage threshold (LIDT), and infrared transparency were measured, and the conversion efficiency, figure of merit (FOM), and energy band structure were calculated for these NCS compound materials. It is found that the NCS materials of SnGa4 Q7 (Q = S, Se) possess large conversion efficiencies, high damage threshold and wide transparencies in the mid-infrared region. Moreover, the study of the micro-mechanism elucidates that the stereochemically active lone-pair electrons of Sn 2+ can significantly improve the polarity of the [SnQ4 ] chromophore. Their large NLO responses originate from the covalent interactions of Sn–Q and the cooperative effects of polarities between the chromophores [SnQ4 ] and [GaQ4 ]. It is also found that the Ba7 Sn5 S15 material has type-I phase- matchability, and that the SHG conversion efficiency and FOM are about twice that of AgGaS2 at the saturated particle size (particle size of 150–212 μm). The Ba8 Sn4 S15 is not a phase-matching material. The SHG intensity and conversion efficiency of Ba8 Sn4 S15 are separately about 250 times those of α-SiO2, and the SHG intensity and conversion efficiency are separately about 10 times those of AgGaS2 at the particle size of 25–45 μm.